Ответ:
[tex] \frac{9b}{(a - b)} \times \frac{ {a}^{2} - ab}{45b} = \frac{9 {a}^{2} b - 9a {b}^{2} }{45b(a - b)} = \frac{9ab(a - b)}{45b(a - b)} = \\ = \frac{9a}{45} [/tex]
при а=-83
[tex] \frac{9 \times ( - 83)}{45} = - 16.6[/tex]
[tex] {(2 - c)}^{2} - c(c + 4) = 4 - 4c + {c}^{2} - {c}^{2} - 4c = \\ = 4 - 8c[/tex]
при с=0.5
[tex]4 - 8 \times 0.5 = 0[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex] \frac{9b}{(a - b)} \times \frac{ {a}^{2} - ab}{45b} = \frac{9 {a}^{2} b - 9a {b}^{2} }{45b(a - b)} = \frac{9ab(a - b)}{45b(a - b)} = \\ = \frac{9a}{45} [/tex]
при а=-83
[tex] \frac{9 \times ( - 83)}{45} = - 16.6[/tex]
[tex] {(2 - c)}^{2} - c(c + 4) = 4 - 4c + {c}^{2} - {c}^{2} - 4c = \\ = 4 - 8c[/tex]
при с=0.5
[tex]4 - 8 \times 0.5 = 0[/tex]